Response of siliceous marine organisms to the Permian-Triassic climate crisis based on new findings from central Spitsbergen, Svalbard - Foster, William (Zenodo, 2023)
Table S2 is the spreadsheet with the identifications of each radiolarian specimen. Table Abundance dataset is the abundance of each radiolarian species in the three investigated samples.